PERAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN JEPARA, TAHUN 2012-2016 - Bono Prambudi (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
This study aims to determine the relationship and influence of the independent variables on the dependent variable, namely investment on economic growth from 2012 to 2016. The data used in this study are data from BPS (Statistics Indonesia). In this study using simple linear regression analysis. The result is that investment is positively related to economic growth. This shows that investment is an important factor in driving economic growth in Jepara Regency